FAKTOR-FAKTOR PENYEBAB KURANG EFEKTIFNYA IMPLEMENTASI KEBIJAKAN BERAS UNTUK RUMAH TANGGA MISKIN DI KELURAHAN BANGKA BELITUNG LAUT KECAMATAN PONTIANAK TENGGARA - Nina Ardiagarini E.01107122 (FISIP Universitas Tanjungpura, 2013)
The research was conducted to investigate the factors that cause the ineffectiveness of policy implementation of rice for poor households (Raskin) in Kelurahan Bangka Belitung Laut Kecamatan Pontianak Tenggara. This is a qualitative research. The data was collected through observation in order to get an overview of the object. Meanwhile the primary data obtained through interviews supported by archival examination, collection of files and documents, and other materials related to the research. To know the validity of the data, the researcher used triangulation method. The results showed that the factors that led to the lack of effectiveness implementation of the policy include: (1) The agents of the policy implementation do not obey the command and the rules; (2) The policy function was not running such as the lateness of the distribution of Raskin and the indiscipline action of the agents in public service; (3) Miss point in achieving the target of Raskin. Based on the research, the advices to be considered are: (1) The understanding and ability of the agent of the policy about Raskin in various kind of things related to the implementation of Raskin policy need to be improved; (2) The need of regular meeting at least once a month between the people in charge of the Raskin policy and the people who receive Raskin is necessity in order to discuss about the program improvement and the problems raised on the field; (3) The delivery of clear information and socialization to the society related to the purposes and advantages of Raskin policy is needed. Keyword: Implementation effectiveness, the obedience of the policy agent, the fluency of the policy function, and the right target.